Analisis Kelayakan Usahatani Komoditas Jahe Gajah Di Desa Tellumpanuae Kecamatan Mallawa Kabupaten Maros - Fahrul Fahrul (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2022)
Abstract— This study aims to determine the feasibility of “Gajah” Ginger Commodity Farming in Tellumpanuae Village, Mallawa District, Maros Regency. This research was conducted in Tellumpanuae Village, Mallawa District, Maros Regency, using the Randong Sampling Method with random sampling with a population of 110 people and 30 people taken. The results of the study explain that the cost of ginger farming is Rp. 655,250 per hectare/planting season, the revenue is Rp. 5,700,000, while the income is Rp. 5,044,750 in Tellumpanuae Village, Mallawa District, Maros Regency. The amount of R/C in ginger farming in Tellumpanuae Village, Mallawa District, Maros Regency is 8.69. For every expenditure of Rp. 1.00, ginger farmers will receive an income of Rp. 7.69. So that “Gajah” ginger farming in Tellumpanuae Village, Mallawa District, Maros Regency is profitable to cultivate.